Measurement of electromagnetic transients in high voltage substations based on wireless transmission technique under strong electromagnetic interference - Ceyong Wang; Lezhi Ou; Wenbing Wu; Chenghui Tan; Yi Ding; Jinxing Zou (Frontiers in Physics)
As power grids expand, the insulation performance of electrical equipment becomes crucial for grid reliability. Thus, measuring transient voltage and current at key substation nodes is essential. Traditional methods are cumbersome and pose electric shock risks with faulty grounding. To address this problem, a wireless-based electromagnetic transient measurement method is proposed in this paper. Firstly, distributed intelligent sensors are placed at various substation points for on-site intelligence. Secondly, a compression algorithm with fault tolerance prevents signal distortion. Then, a distributed wireless synchronous sampling strategy ensures accurate sampling under varying conditions. Finally, field tests show the system achieves high accuracy.